2015
DOI: 10.4103/0972-4052.158080
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of learning module on clinical decision-making in Prosthodontics

Abstract: Purpose:Best practice strategies for helping students learn the reasoning skills of problem solving and critical thinking (CT) remain a source of conjecture, particularly with regard to CT. The dental education literature is fundamentally devoid of research on the cognitive components of clinical decision-making.Aim:This study was aimed to develop and evaluate the impact of blended learning module on clinical decision-making skills of dental graduates for planning prosthodontics rehabilitation.Methodology:An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Therefore, in education, the remaining problem considers didactic methods, which would need to be implemented in the training of future dentists to become therapeutically effective in independent clinical practice, especially in general dentistry. The comparison of the efficacy of teaching methods regarding the ability to decide on prosthetic rehabilitation, with either lecture or discussion in small groups, did not provide any unequivocal response, which of those methods would be more effective way of teaching [15]. In contrast, in a similar study, different results were obtained, showing that working in small groups improves abilities to perform practical procedures compared to lectures.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, in education, the remaining problem considers didactic methods, which would need to be implemented in the training of future dentists to become therapeutically effective in independent clinical practice, especially in general dentistry. The comparison of the efficacy of teaching methods regarding the ability to decide on prosthetic rehabilitation, with either lecture or discussion in small groups, did not provide any unequivocal response, which of those methods would be more effective way of teaching [15]. In contrast, in a similar study, different results were obtained, showing that working in small groups improves abilities to perform practical procedures compared to lectures.…”
Section: Discussionmentioning
confidence: 78%
“…Decision-making in complete denture Prosthodontics is extremely challenging. Each patient presents with a unique yet chronic condition with multiple possible treatment options 12 . It is imperative to involve the patient in prosthodontic decision-making since each treatment option comes with its own share of functional outcomes, cost and complications 7 .…”
Section: Discussionmentioning
confidence: 99%
“…These skills help the young dentists towards better treatment planning of the patients. The findings are in agreement with those of Deshpande et al ., who stated that an improvement in professional ability to plan the treatment efficiently, is required for a successful clinical practice ( Deshpande et al, 2015 ). Findings on communication and interpersonal skills showed that study participants observed a higher score for having sound knowledge of behavioral sciences, interacting professionally with patients, colleagues, and the members of the healthcare team.…”
Section: Discussionmentioning
confidence: 99%